Comparative studies on the immunogenicity of the live spore anthrax vaccine versus non-living vaccine candidates in goats and protective capacity of immune sera in mice - Van Heerden, Henriette (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.